Competitive Coexistence in a Two-Strain Epidemic Model with a Periodic Infection Rate - Chentong Li; Yingying Zhang; Yicang Zhou (Discrete Dynamics in Nature and Society)
In this article, we study the global dynamical behavior of a two-strain SIS model with a periodic infection rate. The positivity and boundedness of solutions are established, and the competitive exclusion conditions are given for the model. The conditions for the global stability of the disease-free equilibrium and persistence of the model are obtained. The conditions of coexistence in this model are also found. Finally, the conditions of uniqueness of the solution are proved.